Degradación del clorotalonilo por un consorcio microbiano aislado de humedales construidos en ensayos de laboratorio (2015)
ABSTRACT: In the laboratory, we evaluated Chlotothalonil degradation by a microbial consortium isolated from the biofilm formed on the gravel of wetlands constructed with a horizontal subsurface flow for treatment of agricultural wastewater, and we estimated the effect of the pesticide on the growth dynamics of the total heterotrophic community and the population of Pseudomonas spp. A chlorothalonil concentration (CLT) of 0,6 mg l-1 and two levels of dissolved organic carbon concentration (COD) of 20 and 100 mg l-1 (employing glucose as a carbon source) were used in the experiments conducted in a solution of synthetic waste water. The response variables were: residual CLT concentration, residual COD concentration, and counts of colony forming units (CFU) of heterotrophic bacteria and Pseudomonas spp. The control variables measured during the process to determine changes in the physicochemical conditions were: electrical conductivity, dissolved oxygen, pH, and redox potential. It was shown that the level of organic carbon concentration notably affected CLT degradation. With 100 mg l-1 of COD, a 99.7% degradation of CLT was attained after 168 h of trial; while 45.1% was attained with 20 mg l-1 of COD. In the chromatographic analysis no degradation products were detected.